Healthcare-seeking practices of African and rural-to-urban migrants in Guangzhou - Bork-Hüffer, Tabea (Journal of current Chinese affairs, 2015)
Taking the examples of Chinese rural-to-urban migrant and African migrant businesspeople in Guangzhou, this article inquires into the commonalities and differences in the health status and healthcare-seeking practices of both groups. While both populations of migrants are diverse and heterogeneous, there are many commonalities with regard to the challenges they face compared to the Chinese local population. Mixed-methods research frameworks and qualitative and quantitative methods were applied. While existing publications emphasise lacking financial access to healthcare, further individual and social factors account for migrants’ healthcare choices. Their access to healthcare can be improved only by introducing insurance schemes with portable benefits, providing localised and culturally adequate health services adapted to migrants’ specific needs and health risks, and enhancing patient orientation and responsiveness by health professionals. (JCCA/GIGA)